Mahkum Fih sebagai Objek Hukum dalam Ushul Fiqih - Nurkhofifah Morra Bilu; Yunistira Y; Rabiaturmania R; Besse Ruhaya (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Mahkum Fih is one of the fundamental concepts in the study of Usul al-Fiqh that refers to the actions of a mukallaf (a legally accountable person) as the object of Islamic legal rulings. Understanding this concept is essential for determining whether an action is classified as obligatory (wajib), recommended (sunnah), prohibited (haram), discouraged (makruh), or permissible (mubah). This paper aims to explain the definition of Mahkum Fih, the requirements for an act to be considered an object of Islamic law, its classifications, the rights associated with it, and its legal foundations in the Qur'an. This study employs a library research method by examining various references on Usul al-Fiqh, Qur'anic exegesis (tafsir), and Islamic legal literature. The findings indicate that Mahkum Fih refers to the actions of a mukallaf that are subject to Islamic legal rulings, provided that the actions are clearly understood by the individual, originate from the commands of Allah SWT and His Messenger, and are within human capability to perform. Mahkum Fih is further classified according to the rights involved, namely the rights of Allah, the rights of human beings, and a combination of both, as well as according to its position within Islamic law. Several Qur'anic verses, including those commanding the establishment of prayer, the payment of zakat, the fulfillment of contracts, and prohibiting adultery and unlawful killing, demonstrate that human actions constitute the object of Islamic law. Therefore, a sound understanding of Mahkum Fih is essential, particularly for students of Usul al-Fiqh, to enable them to comprehend, analyze, and apply Islamic law accurately in daily life and in addressing contemporary legal issues.